Na 2-x Fe 1-x Al x PO4F / C composite material and its preparation and application in sodium ion batteries
By introducing aluminum lattice distortion and carbon-covered structure into the sodium ferrous phosphate positive electrode material, Na2-xFe1-xAlxPO4F/C composite material is prepared by spray-heat treatment process, the problem of poor circulation performance of the material at high magnification is solved, and a positive electrode material with high capacity, excellent magnification performance and stability is achieved.
Patent Information
- Application Number
- CN202110513010.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-05-11
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2041-05-11
AI Technical Summary
The existing sodium ferrous fluorophosphate positive electrode materials have poor discharge capacity and poor circulation performance at high magnification.
The dual strategies of aluminum lattice distortion and carbon coating were adopted to prepare Na2-xFe1-xAlxPO4F/C composite material through spray-heat treatment process, control the Al content and carbon source ratio, and coordinate the heat treatment temperature to improve the capacity, magnification and cyclic stability of the material.
The discharge specific capacity, rate performance and cycle stability of the material have been significantly improved, especially at high magnification, which is close to the performance of theoretical capacity.
Smart Images

Figure BDA0003061006780000071 
Figure HDA0003061006790000011 
Figure HDA0003061006790000012
Abstract
Description
Technical field:
[0001] The present invention relates to the technical field of battery materials, and in particular to the technical field of positive electrode materials for sodium ion batteries. Background technology:
[0002] Lithium-ion batteries have rapidly occupied the portable electronic product market and are constantly penetrating into the field of electric vehicles due to their advantages such as high energy density, high stability, and long life. However, the reserves of lithium resources in the earth's crust are low and the geographical distribution is uneven, which has caused the price of lithium to continue to rise during the large-scale promotion and application of lithium-ion batteries, resulting in high prices for lithium-ion batteries. Therefore, the application of lithium-ion batteries in the field of large-scale power storage is limited. Sodium and lithium belong to the same main group and have similar physical and chemical properties. Sodium resources are abundant, accounting for about 2.64% of the reserves of the earth's crust, and are evenly distributed and low in price. Therefore, research on sodium-ion batteries has gradually received attention.
[0003] In the past few decades, researchers have conducted extensive research on cathode materials for sodium-ion batteries. Among the existing cathode material systems, polyanionic compound systems are considered to be the most commercially promising sodium cathode material systems. Among the polyanionic compound systems, sodium fast ion conductor cathode materials have become a hot topic of research due to their advantages such as good structural stability and thermal stability. The fluorophosphoric acid system provides a two-dimensional channel for ion conduction, which is beneficial to the improvement of discharge stability and capacity. Na2FePO4F has a high theoretical capacity (124mAh·g -1 ) and a stable charge and discharge platform (3.0V), and a stable structure, it is a promising cathode material for sodium ion batteries. However, the capacity of this material has not been fully utilized in existing research, the voltage platform also has room for improvement, and the cycle performance at high rates is poor, which requires further research. Summary of the invention:
[0004] The first object of the present invention is to provide a new Na 2-x Fe 1-x Al x PO4F / C composite material aims to provide a new material with good specific capacity, rate performance and cycle stability.
[0005] The second object of the present invention is to provide a kind of Na 2-x Fe 1-x Al x The preparation process of PO4F / C composite materials aims to reduce lattice collapse, improve crystal phase purity, and improve the electrochemical properties of the prepared materials.
[0006] The third object of the present invention is to provide the Na 2-x Fe1-x Al x Application of PO4F / C composites in sodium-ion batteries.
[0007] The existing sodium ferrous fluorophosphate cathode material has poor discharge capacity and poor cycle performance at high rates. To address this industry problem, the present invention provides the following solutions, mainly in that:
[0008] A Na 2-x Fe 1-x Al x PO4F / C composite material, carbon-coated Na 2-x Fe 1-x Al x A composite material of PO4F, wherein x is 0.05 to 0.15.
[0009] The present invention innovatively provides a completely new material, and finds that based on the Na 2-x Fe 1-x Al x The interaction between PO4F's new physical phase material and carbon coating structure can effectively improve the material's capacity, rate and cycle stability.
[0010] The present invention has found that the innovative use of inert Al(III) to hybridize the lattice can lead to beneficial distortion of the lattice structure, break the order of Na in the structure, and then deintercalate more sodium, which, further combined with the carbon coating, helps to obtain a new material with excellent electrochemical properties.
[0011] The present invention has found that controlling x within a desired ratio is helpful to improve the beneficial lattice distortion caused by Al and to unexpectedly improve the electrochemical properties of the material.
[0012] In the present invention, the carbon content is 3-10wt%.
[0013] The present invention also provides a method for preparing the material, comprising spraying a raw material solution containing a sodium source, an iron source, an aluminum source, a phosphorus source, a fluorine source and a carbon source to obtain a precursor; then heat-treating the precursor under a protective atmosphere to obtain the Na 2-x Fe 1-x Al x PO4F / C composites;
[0014] The molar ratio of carbon source to iron source is 3 to 5:1;
[0015] The temperature of the heat treatment is 500-700°C.
[0016] In the present invention, in order to successfully construct the new material, it is necessary to properly solve the technical problems such as the crystal phase structure transformation and even collapse caused by the Al lattice distortion. In response to this technical problem, the present invention innovatively finds that subjecting the raw materials under the stoichiometric ratio to a spray-heat treatment combined treatment process, and further coordinating the Al content, the proportion of the carbon source and the heat treatment temperature, can help to successfully solve the preparation problems caused by the Al lattice distortion, and help to obtain materials with good crystal phase purity and excellent electrochemical properties.
[0017] In the present invention, the sodium source is at least one of sodium acetate, sodium carbonate, sodium dihydrogen phosphate and sodium bicarbonate.
[0018] Preferably, the iron source is at least one of ferric nitrate and ferrous acetate.
[0019] Preferably, the aluminum source is at least one of aluminum nitrate nonahydrate and aluminum acetate.
[0020] Preferably, the fluoride source is at least one of sodium fluoride, ammonium fluoride, hydrogen fluoride or potassium fluoride.
[0021] Preferably, the phosphorus source is at least one of ammonium dihydrogen phosphate and sodium dihydrogen phosphate.
[0022] Preferably, the sodium source, iron source, aluminum source, phosphorus source and fluorine source are mixed according to the chemical agent ratio.
[0023] The carbon source is at least one of citric acid, ascorbic acid, sucrose and glucose.
[0024] In the present invention, the use of spray-heat treatment means and further coordinated control of the Al content, the carbon source content and the heat treatment temperature are the keys to solving the preparation problem caused by Al(III) lattice distortion, successfully preparing materials, and improving the prepared materials.
[0025] Preferably, x is 0.1 to 0.15.
[0026] Preferably, the molar ratio of the carbon source to the iron source is 3-4:1.
[0027] Preferably, the solvent in the raw material solution is water.
[0028] In the present invention, the spray treatment can be performed based on existing equipment and existing means. The spray operation can be adjusted based on the preparation based on existing principles and means.
[0029] For example, during the spraying process, the inlet temperature is 120-160° C. and the spraying rate is 20-30 ml / min.
[0030] Preferably, the heat treatment temperature is 600-650°C.
[0031] Preferably, the heat treatment time is 8 to 24 hours, more preferably 10 to 12 hours.
[0032] A preferred preparation method of the present invention comprises the following steps:
[0033] (1) a sodium source, an iron source, an aluminum source, a phosphorus source and a fluorine source are prepared in a stoichiometric ratio, mixed with a carbon source in deionized water, and heated and stirred until fully dissolved;
[0034] (2) transferring the solution obtained in step (1) to a nanosprayer for reaction, taking out the powder after the reaction is completed, and placing it in an oven to fully dry to obtain a precursor powder;
[0035] (3) The powder obtained in step (2) is placed in a quartz crucible, calcined at 600-650° C. under a protective atmosphere, and kept warm for 8-24 hours to obtain aluminum-doped carbon-coated sodium ferrous fluorophosphate.
[0036] In order to solve the problems of poor discharge capacity and poor cycle performance at high rate of existing sodium ferrous fluorophosphate positive electrode materials, the present invention adopts aluminum lattice distortion and carbon coating dual strategies, and uses dry spray-heat treatment method to prepare a positive electrode material with high discharge specific capacity, good rate performance and excellent stability.
[0037] The present invention also provides a kind of Na 2-x Fe 1-x Al x Application of PO4F / C composite materials for the preparation of sodium-ion batteries;
[0038] Preferably, it is used as a positive electrode active material for preparing a sodium ion battery.
[0039] The present invention also provides a sodium ion battery positive electrode material, which comprises the Na 2-x Fe 1-x Al x PO4F / C composite material.
[0040] Preferably, the positive electrode material further comprises a binder and a conductive agent. The binder and the conductive agent may be materials known in the industry, for example, the binder may be PVDF, and the conductive agent may be acetylene black. The content of each component may also be adjusted based on existing means, for example, the content of the binder may be 5 to 15 wt%; the content of the conductive agent may be 5 to 15 wt%, and the balance may be the active material (Na 2-x Fe 1-x Al x PO4F / C composite material).
[0041] The present invention also includes a sodium ion battery positive electrode, including a positive electrode current collector and a positive electrode material composited on the surface of the current collector, wherein the positive electrode active material in the positive electrode material includes the Na 2-x Fe 1-x Al x PO4F / C composite material; preferably comprises the positive electrode material.
[0042] The present invention also provides a sodium ion battery, comprising the Na 2-x Fe 1-x Al x PO4F / C composite material; preferably, the positive electrode thereof contains the Na 2-x Fe 1-x Al x PO4F / C composite material.
[0043] Beneficial Effects
[0044] (1) The present invention provides a Na 2-x Fe 1-x Al x The new PO4F compound, based on the lattice distortion effect of Al and the joint control of x, can effectively improve the capacity and cycle performance of the material, especially help to significantly improve the cycle performance at high rates.
[0045] (2) In the present invention, Na 2-x Fe 1-x Al x The in-situ composite of PO4F and C helps to further improve the performance of the material based on the synergy of composition and structure.
[0046] (3) In view of the preparation difficulties caused by Al crystal distortion that need to be overcome in the material preparation process, the present invention innovatively finds that the use of a combined spray-heat treatment process, further based on the coordinated control of the distortion amount and other conditions, can help solve the problems of insufficient crystal phase purity and structural collapse caused by Al distortion, and help obtain new materials with excellent electrochemical properties. Description of the drawings:
[0047] Figure 1 for Na 1.9 Fe 0.9 Al 0.1 XRD diagram of PO4F / C; from the figure, it can be seen that the moderate lattice distortion of Al(III) has resulted in a completely new phase of the material;
[0048] Figure 2 for Na 1.9 Fe 0.9 Al 0.1 SEM image of PO4F / C
[0049] Figure 3 The cycle diagram of the material prepared in Example 1 at 0.1C
[0050] Figure 4 The cycle diagram of the material prepared in Example 2 at 0.1C
[0051] Figure 5 The cycle diagram of the material prepared in Example 3 at 0.1C
[0052] Figure 6 The cycle diagram of the material prepared in Example 4 at 0.1C
[0053] Figure 7 The cycle diagram of the material prepared in Example 5 at 0.1C
[0054] Figure 8 The cycle diagram of the material prepared in Example 6 at 0.1C
[0055] Fig. 9 The cycle diagram of the material prepared in Example 7 at 0.1C
[0056] Fig.10 The cycle diagram of the material prepared in Comparative Example 1 at 0.1C
[0057] Fig.11 The cycle diagram of the material prepared in Comparative Example 2 at 0.1C
[0058] Fig.12 The cycle diagram of the material prepared in Comparative Example 3 at 0.1C
[0059] Fig.13 The cycle diagram of the material prepared in Comparative Example 4 at 0.1C
[0060] Fig.14 The cycle diagram of the material prepared in Comparative Example 5 at 0.1C
[0061] Fig.15 The cycle diagram of the material prepared in Comparative Example 6 at 0.1C
[0062] Fig.16 The cycle diagram of the material prepared in Comparative Example 7 at 0.1C
[0063] Embodiment 1:
[0064] (1) Add ascorbic acid to 50 ml of deionized water and dissolve it completely. Then add Na 1.9 Fe 0.9 Al 0.1The stoichiometric proportion of PO4F is iron nitrate, aluminum nitrate nonahydrate, sodium acetate, ammonium dihydrogen phosphate and sodium fluoride, wherein the molar ratio of ascorbic acid: iron nitrate is 4:1; heated to 30°C and stirred until fully dissolved;
[0065] (2) transferring the solution to a nanosprayer for reaction, setting the inlet temperature to 140°C and the spray rate to 25 ml / min, and obtaining a precursor powder after the reaction is completed;
[0066] (3) The powder was placed in a quartz crucible and heated to 600°C at a rate of 3°C / min under argon and kept at this temperature for 10 h to obtain Na 1.9 Fe 0.9 Al 0.1 PO4F / C composite positive electrode material.
[0067] Embodiment 2:
[0068] Compared with Example 1, the only difference is that in step (1), the molar ratio of ascorbic acid:ferric nitrate is 3:1.
[0069] Embodiment 3:
[0070] Compared with Example 1, the only difference is that in step (1), the molar ratio of ascorbic acid:ferric nitrate is 5:1.
[0071] Embodiment 4:
[0072] Compared with Example 1, the only difference is that in step (1), the aluminum doping amount is different, x=0.05.
[0073] Embodiment 5:
[0074] Compared with Example 1, the only difference is that in step (1), the aluminum doping amount is different, x=0.15.
[0075] Embodiment 6:
[0076] Compared with Example 1, the only difference is that in step (3), the sintering temperature is 500°C.
[0077] Embodiment 7:
[0078] Compared with Example 1, the only difference is that in step (3), the sintering temperature is 700°C.
[0079] Comparative Example 1:
[0080] Compared with Example 1, the only difference is that in step (1), no Al is doped, that is, x=0.
[0081] Comparative Example 2:
[0082] Compared with Example 1, the only difference is that in step (1), the aluminum doping amount is different, that is, x=0.2.
[0083] Comparative Example 3:
[0084] Compared with Example 1, the only difference is that in step (1), no ascorbic acid is added.
[0085] Comparative Example 4:
[0086] Compared with Example 1, the only difference is that in step (1), the molar ratio of ascorbic acid:ferric nitrate is 6:1.
[0087] Comparative Example 5:
[0088] Compared with Example 1, the only difference is that the drying spray is not performed according to step (2), but the traditional sol-gel method is used to stir at 80°C for 6 hours to obtain the gel, and then bake at 120°C for 12 hours to obtain the precursor powder.
[0089] Comparative Example 6:
[0090] Compared with Example 1, the only difference is that in step (3), the sintering temperature is 800°C.
[0091] Comparative Example 7:
[0092] Compared with Example 1, the only difference is that in step (3), the sintering temperature is 450°C.
[0093] The electrical properties of the sodium ferrous fluorophosphate prepared in each embodiment and comparative example were tested:
[0094] The main steps of the test are:
[0095] (1) Using a 2032 model battery case, the positive electrode is a prepared sodium ferrous fluorophosphate electrode (the current collector is aluminum foil, the active material (materials prepared in Examples 1 to 7 and Comparative Examples 1 to 7): conductive carbon (acetylene black): PVDF = 7:2:1), the negative electrode is sodium metal, a fiber separator (model Whatman Grade GF / D) is used, and the electrolyte is 1M NaClO4 (pure PC + 5% FEC) to assemble the battery;
[0096] (2) The rest time is 12 h, and a rate charging program is set, with a rate of 0.1C, a voltage range of 2.0 V-4.0 V, and 50 cycles;
[0097] (3) The theoretical specific capacity of sodium ferrous fluorophosphate is 124 mAh / g;
[0098] The test results are shown in Table 1:
[0099]
[0100] The present invention innovatively provides an Al lattice distortion material, and further finds that through the spray-heat treatment process, further based on the coordinated control of x, carbon source content, and sintering temperature, the crystal phase purity and structure of the lattice distortion material can be improved, which helps to improve the electrochemical properties of the prepared material. In particular, after the introduction of Al (III), the order of Na in the original structure is broken, allowing more sodium to be deintercalated, so that the capacity of the material can be exerted to a level close to the theoretical capacity.
Claims
1. A Na 2-x Fe 1-x Al x The method for preparing a PO4F / C composite material is characterized in that: A raw material solution containing a sodium source, an iron source, an aluminum source, a phosphorus source, a fluorine source and a carbon source is sprayed to obtain a precursor; the precursor is then heat-treated under a protective atmosphere to obtain the Na 2-x Fe 1-x Al x PO4F / C composites; The molar ratio of carbon source to iron source is 3~5:1; The temperature of heat treatment is 500~700℃; The aluminum source is at least one of aluminum nitrate nonahydrate and aluminum acetate; The Na 2-x Fe 1-x Al x PO4F / C composite material is carbon-coated Na 2-x Fe 1-x Al x A composite material of PO4F, wherein x is 0.1 to 0.15; The carbon content is 3-10wt%.
2. Na as claimed in claim 1 2-x Fe 1-x Al x The method for preparing a PO4F / C composite material is characterized in that: The carbon source is at least one of citric acid, ascorbic acid, sucrose and glucose.
3. Na as claimed in claim 1 2-x Fe 1-x Al x The method for preparing a PO4F / C composite material is characterized in that: The sodium source is at least one of sodium acetate, sodium carbonate, sodium dihydrogen phosphate and sodium bicarbonate; The iron source is at least one of ferric nitrate and ferrous acetate; The fluoride source is at least one of sodium fluoride, ammonium fluoride, hydrogen fluoride or potassium fluoride; The phosphorus source is at least one of ammonium dihydrogen phosphate and sodium dihydrogen phosphate; The sodium source, iron source, aluminum source, phosphorus source and fluorine source are mixed according to the chemical agent ratio.
4. Na as claimed in claim 1 2-x Fe 1-x Al x The method for preparing a PO4F / C composite material is characterized in that: The solvent in the raw material solution is water.
5. Na as claimed in claim 1 2-x Fe 1-x Al x The method for preparing a PO4F / C composite material is characterized in that: During the spraying process, the inlet temperature is 120~160℃ and the spraying rate is 20~30ml / min.
6. Na as claimed in claim 1 2-x Fe 1-x Al x The method for preparing a PO4F / C composite material is characterized in that: The heat treatment time is 8~24 h.
7. A Na prepared by the preparation method according to any one of claims 1 to 6 2-x Fe 1-x Al x The application of PO4F / C composite material is characterized by: Used in the preparation of sodium ion batteries.
8. Na as claimed in claim 7 2-x Fe 1-x Al x The application of PO4F / C composite material is characterized by: Used as positive electrode active material for the preparation of sodium ion batteries.
9. A sodium ion battery positive electrode material, characterized in that: It comprises the Na prepared by any one of claims 1 to 6. 2-x Fe 1-x Al x PO4F / C composite material.
10. The sodium ion battery positive electrode material according to claim 9, characterized in that It also contains a binder and a conductive agent.
11. A sodium ion battery, characterized in that: The Na prepared by any one of claims 1 to 6 2-x Fe 1-x Al x PO4F / C composite material.
12. The sodium ion battery according to claim 11, characterized in that The positive electrode contains the Na 2-x Fe 1- x Al x PO4F / C composite material.
Citation Information
Patent Citations
Preparation method and application of aluminum-doped sodium ferrous fluorophosphate positive electrode material
CN118164464A